PELATIHAN PENGGUNAAN APLIKASI GEOGEBRA PADA PEMBELAJARAN MATERI LINGKARAN DI SMPN 10 KOTA SERANG - Huswatun Hasanah (ABDIKARYA: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2020)
The aim of this Community Service Program is to train the students of eighth grade at SMP Negeri 10 Kota Serang to be experts in the use of the Geogebra. The application can make it easier for students to draw geometric shapes so that it makes students better understand math, especially The Circle. The methods are (1) Introduction to the Geogebra application, (2) Explanation of the use of the Geogebra application in mathematics learning, especially The Circle, and (3) Simulation of using the Geogebra application on The Circle. With the increased understanding of The Circle concept and students' expertise in using the Geogebra application hoping students can understand the next concept related to the concept studied.